Detection of Paracetamol in Water and Urea in Artificial Urine with Gold Nanoparticle@Al Foil Cost-efficient SERS Substrate - Mukanova, Zhansaya; Gudun, Kristina; Elemessova, Zarina; Khamkhash, Laura; Ralchenko, Ekaterina; Bukasov, Rostislav (Nihon Bunseki Kagakkai, 2018)
We demonstrated that a cost-efficient, easy to prepare, hybrid SERS substrate-gold nanoparticles (AuNPs) on untreated Al foil (AlF) can effectively detect pharmaceuticals, such as paracetamol and clinical biomarkers, like urea in artificial urine. The limit of detection (LOD) for paracetamol on AuNPs on AlF is superior (0.1 vs. 1 mM ) to the LOD reported for SERS detection of paracetamol in the literature. For SERS detection of urea in urine, AuNPs on both Al foil and Au film performed much better than AuNPs on glass, in terms of the concentration range, linearity and LOD. However, assay on AuNPs on AlF showed a better semi-logarithmic trendline with R2 = 0.98 than an assay on AuNPs on Au film with R2 = 0.94. They have comparable sensitivity with LOD 0.024 and 0.017 M, respectively. The limit of quantification (LOQ) of the former is 0.026 M, which makes it sufficient for the quantification of urea in urine at both normal and pathophysiological (0.03 – 0.15 M) concentration.
https://www.jstage.jst.go.jp/article/analsci/34/2/34_183/_article
Keywords: Research Subject Categories::NATURAL SCIENCES::Chemistry; paracetamol; detection; gold nanoparticle; Surface enhanced Raman spectroscopy; SERS; Al foil